Africa RISING impact assessment report - Haile, Beliyou; Boukaka, Sedi Anne; Azzarri, Carlo (International Food Policy Research Institute, 2024)
This report summarizes lessons from cross-country analyses of the impact of the Africa RISING (AR) program. Implemented in six countries—Ethiopia, Malawi, Tanzania, Zambia, Mali, and Ghana—AR aimed to provide pathways out of hunger and poverty for smallholders by sustainably intensifying their farming systems in order to enhance income and food security, particularly for women and children, while conserving or enhancing the natural resource base. Phase I (2012–2016) focused on the validation of demand-driven sustainable intensification (SI) innovations, while Phase II (2016–2022) focused on the scaling of a subset of validated SI innovations in partnership with development partners.